Catholic Queen, Protestant Patriarchy - Walton, K. author. aut Link
XIII, 220 p. 2 illus.
Keywords: Mary Stuart is infamous for the mysteries of her reign. Mary ruled in a patriarchal society and married a subject; a Catholic queen who was the only person in her kingdom legally allowed to hear Catholic mass. These contradictions in Mary's life forced her contemporaries to search for new answers about how Scotland should be governed.